1981
DOI: 10.1007/bf00225296
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of terminal deoxynucleotidyl transferase activity by thymosin

Abstract: Thymosin fraction 5, a family of acidic polypeptides isolated from bovine thymus, contains several hormonal-like factors which have been shown to influence the maturation, differentiation and functions of T-cells. Some of these peptides have been chemically defined. Two of them, thymosin alpha 1 (M.W. 3108) and thymosin beta 4 (M.W. 4982) have been sequenced. In murine systems, terminal deoxynucleotidyl transferase (TdT) has been shown to be T-cell specific and to be present primarily in the cortisone sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0
2

Year Published

1985
1985
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 23 publications
0
20
0
2
Order By: Relevance
“…Although its role was initially attributed to T cell differentiation (7), it later was found that thymosin β 4 binds to G-actin in a 1:1 complex that prevents monomeric G-actin from polymerizing to filamentous F-actin but supplies a pool of actin monomers inside the cells (12,13). We and others identified thymosin β 4 as an angiogenic factor with activity during HUVEC differentiation in vitro and in vivo (5,(14)(15)(16).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Although its role was initially attributed to T cell differentiation (7), it later was found that thymosin β 4 binds to G-actin in a 1:1 complex that prevents monomeric G-actin from polymerizing to filamentous F-actin but supplies a pool of actin monomers inside the cells (12,13). We and others identified thymosin β 4 as an angiogenic factor with activity during HUVEC differentiation in vitro and in vivo (5,(14)(15)(16).…”
mentioning
confidence: 92%
“…Thymosin β 4 , a 43 amino acid peptide, is the most abundant member of the β-thymosins, a family of highly conserved 5 kD peptides (6). Thymosin β 4 was first isolated from calf thymus and was later found in a variety of tissues and cell types as well as in malignant cells (7)(8)(9)(10)(11). By using cDNA subtractive cloning in an in vitro vessel-forming assay for angiogenesis, thymosin β 4 expression A was increased in human umbilical vein endothelial cells (HUVECs) that were plated on Matrigel compared with HUVECs plated on plastic (5).…”
mentioning
confidence: 99%
“…(34 was originally proposed solely as a thymic hormone, based on its ability to stimulate the T-lymphocyte terminal deoxynucleotidyltransferase after intraperitoneal injection into mice (13,15) and to inhibit macrophage migration at a dosage of 5-500 pM (16). However, later studies indicated that 84 is present at a relatively high abundance in several tissues (17)(18)(19) and cell lines (20,21), raising the possibility that it may also serve a more ubiquitous role.…”
mentioning
confidence: 99%
“…This peptide was reported to show many of the biological activities of thymosin fraction 5 (refs. [9][10][11][12]; for a review, see ref. 6).…”
mentioning
confidence: 99%
“…Prothymosin a was characterized as a highly acidic polypeptide (pI = 3.55) containing approximately 113 amino acid residues with the thymosin a, sequence at its NH2 terminus (18). In the mouse protection test and in assays for lymphokine release, prothymosin a was found to be [10][11][12][13][14][15][16][17][18][19][20] Table 1 is shown in parentheses. The sequence of the first 20 residues is based on the composition of the peptides T1, T2, Thl, and Th2 and the published sequences of thymosin a1 (1) and thymosin a1 (16).…”
mentioning
confidence: 99%